The Difference of Arthropods Diversity in Semi-Organic and Conventional Citrus Orchard in Dau, Malang - Galih El Fikri; Bagyo Yanuwiadi; Aminudin Affandi (Graduate Program, 2019)
The purpose of this research is found diversity of arthropods in citrus orchard to describe effect of pestide. Therefore, the researchers are interested in conducting a study of which is to describe and compare the numbers and types of insects in organic and semi-organic citrus orchard. This study has been done on 4 conventional and 2 semi-organic orchard in Dau, Malang, in February 2019. Arthropod observation using pitfalltraps and visual encounter method. Pitfall trap were performed on 5 point in each orchard. The visual encounter method was conducted for 1 hour in on each orchard. The findings show that there are 1,365 insects which belongs to 10 orders and 21 families. The number of arthropod between the two locations was indicated by the number of different type of arthropods. In the semi-organic orchard, there are 960 Species from 13 families, and conventional there are 405 species from 13 families. The dominant family from Drosopilidae, Formicidae, Chrysomelidae, Lycisidae, Anisolabididae and Aphididae. Conventional orchard system considered as stable environment which is an average of 2.8 of diversity index. The highest number of species belonging to pests reaches 61%.